Main Performance Results of the EDEN ISS Rack-Like Plant Growth Facility - Boscheri, Giorgio; Lamantea, Matteo Maria; Lobascio, Cesare; Volponi, Marco; Schubert, Daniel; Zabel, Paul (47th International Conference on Environmental Systems, 2017)
Giorgio Boscheri, Thales Alenia Space Italia S.p.A., Italy Matteo Maria Lamantea, Thales Alenia Space Italia S.p.A., Italy Cesare Lobascio, Thales Alenia Space Italia S.p.A., Italy Marco Volponi, Politecnico di Torino, Italy Daniel Schubert, German Aerospace Center (DLR), Germany Paul Zabel, German Aerospace Center (DLR), Germany ICES204: Bioregenerative Life Support The 47th International Conference on Environmental Systems was held in South Carolina, USA on 16 July 2017 through 20 July 2017.